Cardiometabolic risk factors among children who are affected by overweight, obesity and severe obesity - Nur Zati Iwani, Ahmad Kamil; Jalaludin, Muhammad Yazid; Roslan, Farah Aqilah; Mansor, Fazliana; Md Zain, Fuziah; Hong, Janet Yeow Hua; Zin, Ruziana Mona Wan Mohd; Yahya, Abqariyah; Ishak, Zahari; Selamat, Rusidah; Mokhtar, Abdul Halim (Frontiers in Public Health, 2023)
Background The increasing severity of obesity is expected to lead to more serious health effects. However, there is limited information on the prevalence and clinical characteristics of cardiometabolic risk factors in severely children affected by obesity in Malaysia. This baseline study aimed to investigate the prevalence of these factors and their association with obesity status among young children. Methods In this study, a cross-sectional design was employed using the baseline data obtained from the My Body Is Fit and Fabulous at school (MyBFF@school) intervention program involving obese school children. Obesity status was defined using the body mass index (BMI) z-score from the World Health Organization (WHO) growth chart. Cardiometabolic risk factors presented in this study included fasting plasma glucose (FPG), triglycerides (TGs), total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), blood pressure, acanthosis nigricans, insulin resistance (IR), and MetS. MetS was defined using the International Diabetes Federation (IDF) 2007 criteria. Descriptive data were presented accordingly. The association between cardiometabolic risk factors, such as obesity status, and acanthosis nigricans with MetS was measured using multivariate logistic regression, which was adjusted for gender, ethnicity, and strata. Results Out of 924 children, 38.4% (n = 355) were overweight, 43.6% (n = 403) were obese, and 18% (n = 166) were severely obese. The overall mean age was 9.9 ± 0.8 years. The prevalence of hypertension, high FPG, hypertriglyceridemia, low HDL-C, and the presence of acanthosis nigricans among severely children affected by obesity was 1.8%, 5.4%, 10.2%, 42.8%, and 83.7%, respectively. The prevalence of children affected by obesity who were at risk of MetS in <10-year-old and MetS >10-year-old was observed to be similar at 4.8%. Severely children affected by obesity had higher odds of high FPG [odds ratio (OR) = 3.27; 95% confdence interval (CI) 1.12, 9.55], hypertriglyceridemia (OR = 3.50; 95%CI 1.61, 7.64), low HDL-C (OR = 2.65; 95%CI 1.77, 3.98), acanthosis nigricans (OR = 13.49; 95%CI 8.26, 22.04), IR (OR = 14.35; 95%CI 8.84, 23.30), and MetS (OR = 14.03; 95%CI 3.97, 49.54) compared to overweight and children affected by obesity. The BMI z-score, waist circumference (WC), and percentage body fat showed a significant correlation with triglycerides, HDL-C, the TG: HDL-C ratio, and the homeostatic model assessment for IR (HOMA-IR) index. Conclusions Severely children affected by obesity exhibit a higher prevalence of and are more likely to develop cardiometabolic risk factors compared to overweight and children affected by obesity. This group of children should be monitored closely and screened periodically for obesity-related health problems to institute early and comprehensive intervention.